The Effect of Using Crossword Puzzle Towards Students’ Vocabulary Mastery in the Eleventh Grade Students of SMA Muhammadiyah 2 Bandar Lampung in Academic Year 2017-2018 - Melasari, Melasari; Ismawati, Krisna; Nanda, Deri Sis (Journal of English Education Studies, 2019)
This research describes the use of Crossword Puzzle to improve students’ vocabulary mastery. Moreover, it was to find out whether Crossword Puzzle is effective to improve students’ vocabulary mastery at the second grade students of SMA Muhammadiyah 2 Bandar Lampung. This research used experimental design in which the samples of the research were assessed both before and after an experimental treatment. The subject of the research consisted of 68 students, they were divided into experimental and control group. The instruments used for collecting the data were test which was consisted of pretest and posttest. The data analysis of this research was attempted by using independent sample T-test which was calculated through computing with statistical package for Social Science (SPSS) version 20.The result indicated that the students’ mean score of experimental and control group in post-test were significantly different. It showed that t-count was higher than t-table (4.454 > 1.9966) and the sig. 2-tailed value was lower than sig. Level (0.000 > 0.05). Therefore the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It meant that there was effective impact of using crossword puzzle towards students’ vocabulary mastery. Decision based on facts, using crossword puzzle as a technique was effective to improve students’ vocabulary. Therefore, it was suggested the use of crossword puzzle as a technique in teaching English generally and teaching Vocabulary specifically